Is Generation Z Willing to Consume Halal-Certified Products to Support Sustainable Development? - Abdullah, Abdullah; Hasan Bisri; Jeyhan Ali Azhar; Akmal Asman (El-Qish: Journal of Islamic Economics, 2025)
This research aims to determine Gen Z's desire to consume halal-certified products to support sustainable development. This study uses a questionnaire and expands the TPB theory popularized by Ajzen by adding religiousness and halal literacy variables, which aim to measure the extent to which these variables have an impact on the research object. The analytical model for this research (PLS-SEM) was adopted to test the research model on 357 samples obtained from five islands in Indonesia. The research results show that, first, testing perceived behavioral control and attitude has a significant effect on religiousness, while subjective norms and halal literacy do not have a significant effect on religiousness. Second, perceived behavioral control, attitude, subjective norms, and halal literacy have a significant effect on the willingness to consume sustainable development. Third, the religious variable does not show significant results on the willingness to consume sustainable development. This research proposes implications that emphasize increasing halal literacy for Gen Z throughout Indonesia by providing broad accessibility for an integral understanding of halal.